Comparative transcriptome sequencing of germline and somatic tissues of the Ascaris suum gonad - Ma, Xuan (BioMed Central, 2011)
BACKGROUND: Ascaris suum (large roundworm of pigs) is a parasitic nematode that causes substantial losses to the meat industry. This nematode is suitable for biochemical studies because, unlike C. elegans, homogeneous tissue samples can be obtained by dissection. It has large sperm, produced in great numbers that permit biochemical studies of sperm motility. Widespread study of A. suum would be facilitated by more comprehensive genome resources and, to this end, we have produced a gonad transcriptome of A. suum. RESULTS: Two 454 pyrosequencing runs generated 572,982 and 588,651 reads for germline (TES) and somatic (VAS) tissues of the A. suum gonad, respectively. 86% of the high-quality (HQ) reads were assembled into 9,955 contigs and 69,791 HQ reads remained as singletons. 2.4 million bp of unique sequences were obtained with a coverage that reached 16.1-fold. 4,877 contigs and 14,339 singletons were annotated according to the C. elegans protein and the Kyoto Encyclopedia of Genes and Genomes (KEGG) protein databases. Comparison of TES and VAS transcriptomes demonstrated that genes participating in DNA replication, RNA transcription and ubiquitin-proteasome pathways are expressed at significantly higher levels in TES tissues than in VAS tissues. Comparison of the A. suum TES transcriptome with the C. elegans microarray dataset identified 165 A. suum germline-enriched genes (83% are spermatogenesis-enriched). Many of these genes encode serine/threonine kinases and phosphatases (KPs) as well as tyrosine KPs. Immunoblot analysis further suggested a critical role of phosphorylation in both testis development and spermatogenesis. A total of 2,681 A. suum genes were identified to have associated RNAi phenotypes in C. elegans, the majority of which display embryonic lethality, slow growth, larval arrest or sterility. CONCLUSIONS: Using deep sequencing technology, this study has produced a gonad transcriptome of A. suum. By comparison with C. elegans datasets, we identified sets of genes associated with spermatogenesis and gonad development in A. suum. The newly identified genes encoding KPs may help determine signaling pathways that operate during spermatogenesis. A large portion of A. suum gonadal genes have related RNAi phenotypes in C. elegans and, thus, might be RNAi targets for parasite control.